The influence of pitch dimensions on performance during small-sided and conditioned soccer games - Vilar, L.; Duarte, R.; Silva, P.; Chow, J. Y.; Davids, K. (Journal of Sports Sciences, 2014)
This study examined the influence of pitch dimensions in small-sided soccer games in shaping opportunities for performers to maintain ball possession, pass to teammates and shoot at goal. Fifteen amateur standard male participants (M = 21.87, s = 1.96 years) played 5 v 5 small-sided soccer games in three varying pitch conditions (28 m × 14 m, 40 m × 20 m and 52 m × 26 m). Thirty sequences of play in each condition were selected for digitisation using TACTO software, allowing the capture of bi-dimensional displacement coordinate data of all players and the ball. The values of interpersonal distance between all attackers and immediate defenders and the relative distances of defenders to intercept a shot and a pass were computed as dependent variables. Results showed existence of fewer opportunities to maintain ball possession on smaller pitches, compared to medium and larger pitches. Conversely, the different dimensions set to the pitch did not influence opportunities for players to shoot at goal, or to perform passes to other teammates. By examining the specific spatial-temporal relationships of players and key-task constraints, the data from this study explain how effects of manipulating pitch dimensions of small-sided games might enhance opportunities for acquiring specific movement and decision-making skills.